Benchmarking practices among single sex boarding secondary schools in Western Kenya - Jane Amunga (Technium Social Sciences Journal, 2020)
This study investigated benchmarking practices by single sex boarding secondary schools in the Western region of Kenya. The purpose was to establish why these schools engaged in benchmarking, whether they prioritised different or common benchmarking activities, and the factors militating against benchmarking. The study was guided by the theory of the learning organization. The target was 66 (37 Boys boarding and 29 Girls boarding schools, previously classified as provincial schools) engaged in benchmarking at the time of the study. A total of 20 schools representing 30% were randomly selected. Of the 240 who formed the study sample (20 principals, 20 DOSs, 100 HODs and 100 teachers) 215 (89.58%) responded. Data were collected using questionnaires with closed and open ended items, and analysed both descriptively (means and percentages) and inferentially (Chi-square and Z-test) using the Predictive Analytical Software (PASW) Version 19.0. All responses on the open ended questions were paraphrased and others reported verbatim in triangulation of findings. The study found that, schools benchmarked national and county schools. Most of the programmes benchmarked were targeted improvement in academic performance. Both categories of schools had common benchmarking interests and therefore sought information on similar practices and programmes. While most respondents reported it the practice had improved examination results, a number of challenges were pointed out. These were lack of time, lack of resources, too much focus on exams and poor implementation of benchmarked programmes. It was therefore recommended that, schools create ample time for the exercise, allocate sufficient resources for implementation of programmes and go beyond the focus on academics to benchmark on other practices that build an all round student.